Firma w nowej koncepcji gospodarki - Krawiec, Frank (Firm in the New Economy, 2005)
This paper presents a contemporary firm in the new economy. Both key characteristics and rules of performance are also discussed in this conference paper. New economy is based on information or on digital network systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 249-272